Intelligent Bimetallic Nanoagents as Reactive Oxygen Species Initiator System for Effective Combination Phototherapy - Li, Hongfeng; Li, Ying; Xiang, Jingjing; Yang, Xing; Li, Chunbing; Liu, Chuangjun; Zhao, Qi; Zhou, Lihua; Gong, Ping; Huang, Jiahao (Frontiers in Bioengineering and Biotechnology, 2020)
Phototherapy is a promising oncotherapy method. However, there are various factors greatly restricted phototherapy development, including poor tumor-specific accumulation, the hypoxia in solid tumor, and the systemic phototoxicity of photosensitizer. Herein, a tumor microenvironment (TME)-responsive intelligent bimetallic nanoagents (HSA-Pd-Fe-Ce6 NAs) composed of human serum albumin (HSA), palladium-iron (Pd-Fe) bimetallic particles, and chlorin e6 (Ce6) was designed for effective combination phototherapy. The Pd-Fe part in the HSA-Pd-Fe-Ce6 NAs would react with the endogenous hydrogen peroxide (H2O2) in an acidic ambience within tumor to generate cytotoxic superoxide anion free radical through the "Fenton-like reaction". H2O2, coupled with highly toxic singlet oxygen (1O2) caused by the Ce6 component under the irradiation of 660 nm laser, resulted in synergistic cancer therapy effects in hypoxia surroundings. Besides, this nanoagents could result in hyperpyrexia-induced cell apoptosis because of superior absorption performance in near-infrared wavelength window bringing about excellent photothermal conversion efficiency. The cell cytotoxicity results showed that the survival rate after treated by 40 μg mL-1 nanoagents was only 17%, which reveals that the HSA-Pd-Fe-Ce6 NAs had the advantage of efficient and controllable phototherapy. In short, it exhibited excellent hypoxia-resistant combination phototherapy efficacy in vitro. Therefore, the multifunctional nanoagents are powerful and provide a new avenue for effective combination phototherapy.